STATUS OF THE IMAGING SPECTROSCOPY MISSION ENMAP WITH RADIOMETRIC CALIBRATION AND CORRECTION - T. Storch; H.-P. Honold; K. Alonso; M. Pato; M. Mücke; P. Basili; S. Chabrillat; S. Fischer (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
The high-resolution imaging spectroscopy remote sensing mission EnMAP (Environmental Mapping and Analysis Program, enmap.org) covers the spectral range from 420 nm to 2450 nm with a spectral sampling distance varying between 4.8 nm and 12.0 nm comprising 262 spectral bands. We focus on the planned framework concerning radiometry. The expected signal-to-noise ratio at reference radiance level is 500:1 at 495 nm and 150:1 at 2200 nm. The radiometric resolution is 14 bits and an absolute radiometric accuracy of better than 5% is achieved. Radiometric calibration is based on Sun calibration measurements with a fullaperture diffusor for absolute calibration. In addition, relative calibration monitors the instrument during the complete mission lifetime based on an integrating sphere (on the satellite). The fully-automatic on-ground image processing chain considers the derived radiometric calibration coefficients in the radiometric correction which is followed by the orthorectification and atmospheric compensation. Each of the two 2-dimensional detector arrays of the prism-based pushbroom dual-spectrometer works in a dual-gain configuration to cover the complete dynamic range. EnMAP will acquire 30 km in the across-track direction with a ground sampling distance of 30 m and the across-track tilt capability of 30° will enable a target revisit time of less than 4 days. The launch is scheduled for 2021. The high-quality products will be freely available to international scientific users for measuring and analysing diagnostic parameters which describe vital processes on the Earth’s surface.